2012
DOI: 10.15407/spqeo15.03.239
|View full text |Cite
|
Sign up to set email alerts
|

The factors influencing luminescent properties of ZnS:Mn obtained by the method of one-stage synthesis

Abstract: Abstract. Considered in this paper is the model that combines appearance of defects responsible for self-activated (SA) emission in ZnS with its piezoelectric properties. Being based on analysis of the luminescence spectrum, the authors demonstrate the influence of mechanical destruction, impact of ultrasound, microwave radiation and pulsed magnetic field on the emission efficiency for centers of luminescence connected with intrinsic defects in ZnS:Mn prepared using the method of self-propagating hightemperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Bacherikov et al [45] have reported the factors influencing luminescent properties of ZnS:Mn nanoparticles obtained by the method of one-stage synthesis. They have proposed a model that combines appearance of defects responsible for self-activated (SA) emission in ZnS with its piezoelectric properties.…”
Section: Introductionmentioning
confidence: 99%
“…Bacherikov et al [45] have reported the factors influencing luminescent properties of ZnS:Mn nanoparticles obtained by the method of one-stage synthesis. They have proposed a model that combines appearance of defects responsible for self-activated (SA) emission in ZnS with its piezoelectric properties.…”
Section: Introductionmentioning
confidence: 99%